Learning anatomy through Thiel‐ vs. formalin‐embalmed cadavers: Student perceptions of embalming methods and effect on functional anatomy knowledge. Issue 2 (18th July 2017) - Kennel, Larissa; Martin, David M. A.; Shaw, Hannah; Wilkinson, Tracey
Abstract : Thiel‐embalmed cadavers, which have been adopted for use in anatomy teaching in relatively few universities, show greater flexibility and color retention compared to formalin‐embalmed cadavers, properties which might be considered advantageous for anatomy teaching. This study aimed to investigate student attitudes toward the dissection experience with Thiel‐ compared to formalin/ethanol‐embalmed cadavers. It also aimed to determine if one embalming method is more advantageous in terms of learning functional anatomy through the comparison of student anterior forearm functional anatomy knowledge. Student opinions and functional anatomy knowledge were obtained through use of a questionnaire from students at two medical schools, one using Thiel‐, and one using more traditional formalin/ethanol‐embalmed cadavers. Both the Thiel group and the formalin group of students were surveyed shortly after completing an anterior forearm dissection session. Significant differences ( P ‐values <0.01) in some attitudes were found toward the dissection experience between cohorts using Thiel‐ vs. formalin‐embalmed cadavers. The Thiel group of students felt more confident about recognizing anatomy in the living individual, found it easier to identify and dissect anatomical structures, and indicated more active exploration of functional anatomy due to the retained flexibility of the cadaver. However, on testing, no significant difference in functional anatomy knowledge was found between the two cohorts. Overall, although Thiel embalming may provide an advantageous learning experience in some investigated areas, more research needs to be carried out, especially to establish whether student perception is based on reality, at least in terms of structure identification. Anat Sci Educ 11: 166–174. © 2017 American Association of Anatomists.